2011
DOI: 10.1080/03069885.2010.531383
|View full text |Cite
|
Sign up to set email alerts
|

Working with clients who engage in self-harming behaviour: experiences of a group of counsellors

Abstract: This study aimed to explore the experiences of a group of counsellors regarding working with clients who engage in self-harming behaviour, in order to gain an understanding of what it is like to work with this client group. A series of six individual, semi-structured qualitative interviews were carried out, which were then transcribed and analysed using thematic analysis. Counsellors' experiences were characterised by a number of themes, including the nature of self-harm, in terms of severity and vividness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…In a qualitative study, Doucette (2004) explored the benefits of walk and talk therapy for behaviourally challenged youths by conducting interviews with clients and found that the impact of therapy was enhanced by being outdoors and engaging in exercise and that the walking component allowed for physical release and aided problem-solving. Studies of professional knowledge, in which practitioners report on their experience in relation to a specific area of work, represent a valuable research strategy in emerging areas of practice (Chartas & Culbreth, 2001;Christianson & Everall, 2009;Finn & Barak, 2010;Fox, 2011;Karakurt, Dial, Korkow, Manfield & Banford, 2013;van Rooij, Zinn, Schoenmakers & van de Mheen, 2012). To date, one professional knowledge study has been carried out in the area of walk and talk.…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative study, Doucette (2004) explored the benefits of walk and talk therapy for behaviourally challenged youths by conducting interviews with clients and found that the impact of therapy was enhanced by being outdoors and engaging in exercise and that the walking component allowed for physical release and aided problem-solving. Studies of professional knowledge, in which practitioners report on their experience in relation to a specific area of work, represent a valuable research strategy in emerging areas of practice (Chartas & Culbreth, 2001;Christianson & Everall, 2009;Finn & Barak, 2010;Fox, 2011;Karakurt, Dial, Korkow, Manfield & Banford, 2013;van Rooij, Zinn, Schoenmakers & van de Mheen, 2012). To date, one professional knowledge study has been carried out in the area of walk and talk.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion might consider how the attitudes and beliefs of the practitioner can influence communication and the therapeutic relationship with a client (Saunders et al., ). This might also provide an early point of intervention for stigma reduction (Anderson et al., ; Fox, ). Despite limitations and the exploratory nature of the study, counselling student attitudes towards self‐harm warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Type of self-harm appears to have an effect on counselling student response. Previous research has also found severity to have an impact on the counsellor themselves (Fox, 2011). It would seem appropriate to allow time and space during training to explore thoughts and feelings around self-harm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored and described adults’ perceptions and attitudes towards deliberate self-harm. Most of the existing literature has focused on the perspectives of parents of adolescents who self-harm (Ferrey et al, 2016; McDonald, O'Brien, & Jackson, 2007; Oldershaw, Richards, Simic, & Schmidt, 2008; Rissanen, Kylmä, & Laukkanen, 2009), healthcare professionals (Karman, Kool, Poslawsky, & Van Meijel, 2015; Lindgren, Oster, Aström, & Graneheim, 2011; McHale & Felton, 2010; Rees, Rapport, Thomas, John, & Snooks, 2014), counsellors (De Stefano, Atkins, Noble, & Heath, 2012; Fox, 2011; Long & Jenkins, 2010), and teachers (Berger, Hasking, & Reupert, 2014; Heath, Toste, & Beettam, 2007; Heath, Toste, Sornberger, & Wagner, 2011).…”
mentioning
confidence: 99%